Moving beyond Definitive Therapy: Increasing Physical Activity in Survivors of Cancers of the Head and Neck - Anthony D. Nehlsen; Kunal K. Sindhu; Brianna M. Jones; Eric J. Lehrer; Jared P. Rowley; Richard L. Bakst (Current Oncology, 2022)
As chemotherapeutic, radiation, and surgical techniques have improved, there has been a dramatic improvement in survival in patients diagnosed with cancers of the head and neck. As a result, a heightened focus on survivorship by clinicians will increasingly prove necessary. In particular, medical care teams will have to pay special attention to mitigating the long-term sequelae of definitive cancer treatments, many of which act as barriers to exercise. This is unfortunate, as the benefits of exercise in patients with cancer have become increasingly recognized. In this review, we discuss the potential benefits of and barriers to exercise in survivors of cancers of the head and neck. We also review existing exercise guidelines and strategies by which clinicians can promote exercise in this unique patient population.